Adiponectin/leptin ratio as a predictor of acute rejection in early post-transplant period in patients after kidney transplantation - Graňák, Karol; Vnučák, Matej; Beliančinová, Monika; Kleinová, Patrícia; Pytliaková, Margaréta; Mokáň, Marián; Dedinská, Ivana (Frontiers in Medicine, 2023)
Introduction Adipokines are largely involved in the regulation of immune system activity. While leptin is the main pro-inflammatory marker of adipose tissue, adiponectin is characterized by anti-inflammatory effects. The aim of our study was to determine the risk of acute graft rejection in protocol biopsy depending on the adiponectin/leptin (A/L) ratio in patients after kidney transplantation (KT). Materials and methods A total of 104 patients were included in the prospective analysis, in whom the levels of adipokines were examined pre-transplant, in the 3rd month after KT and the A/L ratio was calculated. In the 3rd month after KT, all patients underwent protocol biopsy of the graft and examination of donor-specific antibodies (DSA) using the Luminex method. Results After adjusting for differences in the basic characteristics of the donor and recipient, we identified a subgroup with A/L ratio < 0.5 pre-transplant [HR 1.6126, (P = 0.0133)] and 3 months after KT [HR 1.3150, (P = 0.0172)] as independent risk factor for acute graft rejection. In the subsequent specification of the rejection episode, we identified the risk ratio A/L < 0.5 before KT [HR 2.2353, (P = 0.0357)] and 3 months after KT [HR 3.0954, (P = 0.0237)] as independent risk factor for the development of acute humoral rejection with DSA positivity. Conclusion This is the first study to investigate the relationship between A/L ratio and immunological risk in terms of the development of rejection changes in patients after KT. In our study, we found that A/L ratio < 0.5 is an independent risk factor for the development of acute humoral rejection and de novo DSA production in the third month after KT.